Left-handedness and risk of breast cancer - Fritschi, L (Nature Publishing Group, 2007)
Left-handedness may be an indicator of intrauterine exposure to oestrogens, which may increase the risk of breast cancer. Women (n=1786) from a 1981 health survey in Busselton were followed up using death and cancer registries. Left-handers had higher risk of breast cancer than right-handers and the effect was greater for post-menopausal breast cancer (hazard ratio=2.59, 95% confidence interval 1.11–6.03).